Pregunta
upstudy study bank question image url

Write a polynomial with the following given zeros (roots): \( -2,-3,4-3 i \)

Ask by Stuart Ramirez. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The polynomial with zeros –2, –3, and 4 – 3i is \( P(x) = x^4 - 3x^3 - 9x^2 + 77x + 150 \).

Solución

We are given the zeros –2, –3, and 4 – 3i. Since we want a polynomial with real coefficients, we must include the complex conjugate of 4 – 3i, which is 4 + 3i, as a zero. Step 1. Write the linear factors corresponding to each zero:   Factor 1: (x + 2)   Factor 2: (x + 3)   Factor 3: (x – (4 – 3i))  = (x – 4 + 3i)   Factor 4: (x – (4 + 3i))  = (x – 4 – 3i) Step 2. Multiply the complex conjugate factors first:   (x – 4 + 3i)(x – 4 – 3i) This product is of the form (a + b)(a – b) = a² – b², where a = x – 4 and b = 3i. Thus,   = (x – 4)² – (3i)²   = (x – 4)² – (–9)    [since (3i)² = –9]   = (x – 4)² + 9 Expanding (x – 4)²:   = x² – 8x + 16 + 9   = x² – 8x + 25 Step 3. Now multiply with the remaining factors (x + 2) and (x + 3). First, combine them:   (x + 2)(x + 3) = x² + 5x + 6 Step 4. Multiply the quadratic factors:   (x² + 5x + 6)(x² – 8x + 25)   Performing the multiplication:    x²·x² = x⁴    x²·(–8x) = –8x³    x²·25 = 25x²    5x·x² = 5x³    5x·(–8x) = –40x²    5x·25 = 125x    6·x² = 6x²    6·(–8x) = –48x    6·25 = 150 Now, combine like terms:   x⁴ term: x⁴   x³ terms: (–8x³ + 5x³) = –3x³   x² terms: (25x² – 40x² + 6x²) = –9x²   x terms: (125x – 48x) = 77x   Constant: 150 Thus, the polynomial is:   P(x) = x⁴ – 3x³ – 9x² + 77x + 150 This is a monic polynomial with the given zeros.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To construct a polynomial with the given roots \( -2, -3, \) and \( 4 - 3i \), we first note that complex roots occur in conjugate pairs. Therefore, the conjugate \( 4 + 3i \) is also a root. The polynomial can be expressed as: \[ P(x) = (x + 2)(x + 3)(x - (4 - 3i))(x - (4 + 3i)) \] Now, simplifying the complex pair: \[ (x - (4 - 3i))(x - (4 + 3i)) = ((x - 4) + 3i)((x - 4) - 3i) = (x - 4)^2 + 9 \] Expanding it gives: \[ (x - 4)^2 + 9 = x^2 - 8x + 16 + 9 = x^2 - 8x + 25 \] Now putting it all together: \[ P(x) = (x + 2)(x + 3)(x^2 - 8x + 25) \] We can multiply out the first two factors: \[ (x + 2)(x + 3) = x^2 + 5x + 6 \] Now the polynomial becomes: \[ P(x) = (x^2 + 5x + 6)(x^2 - 8x + 25) \] Next, we expand this: 1. \( x^2 \cdot (x^2 - 8x + 25) = x^4 - 8x^3 + 25x^2 \) 2. \( 5x \cdot (x^2 - 8x + 25) = 5x^3 - 40x^2 + 125x \) 3. \( 6 \cdot (x^2 - 8x + 25) = 6x^2 - 48x + 150 \) Combining these, we find: \[ P(x) = x^4 - 3x^3 + 81x^2 + 125x + 150 \] So the polynomial with the given roots is: \[ P(x) = x^4 - 3x^3 + 81x^2 + 125x + 150 \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad